A will-o’-the wisp? On the utility of voluntary contributions of data and knowledge from the fishing industry to marine science - Steins, Nathalie A.; Mackinson, Steven; Mangi, Stephen C.; Pastoors, Martin A.; Stephenson, Robert L.; Ballesteros, Marta; Brooks, Kate; McIsaac, James A.; Baker, Matthew R.; Calderwood, Julia; Neis, Barbara; Ogier, Emily M.; et al. (Frontiers in Marine Science, 2022)
For future sustainable management of fisheries, we anticipate deeper and more diverse information will be needed. Future needs include not only biological data, but also information that can only come from fishers, such as real-time ‘early warning’ indicators of changes at sea, socio-economic data and fishing strategies. The fishing industry, in our experience, shows clear willingness to voluntarily contribute data and experiential knowledge, but there is little evidence that current institutional frameworks for science and management are receptive and equipped to accommodate such contributions. Current approaches to producing knowledge in support of fisheries management need critical re-evaluation, including the contributions that industry can make. Using examples from well-developed advisory systems in Europe, United States, Canada, Australia and New Zealand, we investigate evidence for three interrelated issues inhibiting systematic integration of voluntary industry contributions to science: (1) concerns about data quality; (2) beliefs about limitations in useability of unique fishers’ knowledge; and (3) perceptions about the impact of industry contributions on the integrity of science. We show that whilst these issues are real, they can be addressed. Entrenching effective science-industry research collaboration (SIRC) calls for action in three specific areas; (i) a move towards alternative modes of knowledge production; (ii) establishing appropriate quality assurance frameworks; and (iii) transitioning to facilitating governance structures. Attention must also be paid to the science-policy-stakeholder interface. Better definition of industry’s role in contributing to science will improve credibility and legitimacy of the scientific process, and of resulting management.